Financial Cerdas, Bebas Risiko: Workshop Literasi Keuangan dan Hukum Digital untuk Ibu-Ibu PKK Kecamatan Sui Raya Kabupaten Kubu Raya - Febrianawati; Yenny Aman Serah; Uray, Andrey Indra Maulana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
A low understanding of digital financial management, the risks of online fraud, and the legal aspects of digital transactions prompted the Community Service Program themed “Smart Finance, Risk-Free: Workshop on Financial and Digital Legal Literacy for PKK Mothers in Sui Raya District, Kubu Raya Regency.” The main objective of this activity is to enhance the understanding and skills of PKK mothers in managing finances digitally in a safe and efficient manner, to raise awareness about the dangers of online fraud and prevention methods, and to provide knowledge about personal data protection and digital legal aspects. The method used is an interactive workshop that includes material presentation, discussions, and hands-on practice with financial applications. The targeted outcomes include an increase in participants' understanding, as measured by pre-test and post-test results, with a minimum improvement of 20% in financial literacy and 15% in digital legal literacy. Additional outcomes include documentation of the activities in the form of a video uploaded to online mass media platforms and the publication of the results in a scientific journal on PKM. This program equips participants to be able to optimally utilize digital technology and avoid financial and legal risks.